Female transgressor body: Art created as a denunciation of violence against women in a dialogue with Artemisia Gentilesch - Casoli, Rosemery (Revista do Colóquio, 2021)
In this article, we intend to analyze in an investigative way, two works by the painter Artemisia Gentilesch, with the objective of proposing a reflection on the feminine artistic creations used as demarcations of denunciation and transgression in the context of the imposition of inferiority of woman. Presenting some personal perceptions resulting from the research process that we use, we will list in this article the importance of verbalizing the violence suffered as an auxiliary tool to transgress the current rules of domination of women. It will also be sought to emphasize that the fight against violence needs to be worked on in the subject-woman so that there is a result of self-worth essential for each woman to recognize herself as a transgressor female body.
Keywords: Art; Woman; Denunciation; Confronting violence; Transgression